The Mycobacterium avium ssp. paratuberculosis specific mptD gene is required for maintenance of the metabolic homeostasis necessary for full virulence in mouse infections - Meiß, Thorsten; Eckelt, Elke; Basler, Tina; Meens, Jochen; Heinzmann, Julia; Suwandi, Abdulhadi; Oelemann, Walter M. R.; Trenkamp, Sandra; Holst, Otto; Weiss, Siegfried; Bunk, Boyke; Spröer, Cathrin; et al. (Frontiers in Cellular and Infection Microbiology, 2014)
Mycobacterium avium subspecies paratuberculosis (MAP) causes Johne's disease, a chronic granulomatous enteritis in ruminants. Furthermore, infections of humans with MAP have been reported and a possible association with Crohn's disease and diabetes type I is currently discussed. MAP owns large sequence polymorphisms (LSPs) that were exclusively found in this mycobacteria species. The relevance of these LSPs in the pathobiology of MAP is still unclear. The mptD gene (MAP3733c) of MAP belongs to a small group of functionally uncharacterized genes, which are not present in any other sequenced mycobacteria species. mptD is part of a predicted operon (mptABCDEF), encoding for a putative ATP binding cassette-transporter, located on the MAP-specific LSP14. In the present study, we generated an mptD knockout strain (MAPΔmptD) by specialized transduction. In order to investigate the potential role of mptD in the host, we performed infection experiments with macrophages. By this we observed a significantly reduced cell number of MAPΔmptD early after infection, indicating that the mutant was hampered with respect to adaptation to the early macrophage environment. This important role of mptD was supported in mouse infection experiments where MAPΔmptD was significantly attenuated after peritoneal challenge. Metabolic profiling was performed to determine the cause for the reduced virulence and identified profound metabolic disorders especially in the lipid metabolism of MAPΔmptD. Overall our data revealed the mptD gene to be an important factor for the metabolic adaptation of MAP required for persistence in the host.